2020
DOI: 10.1016/j.jwpe.2020.101664
|View full text |Cite
|
Sign up to set email alerts
|

Review on discharge Plasma for water treatment: mechanism, reactor geometries, active species and combined processes

Abstract: Owing to the water crisis, the development of innovative and clean advanced oxidation processes to decompose a variety of harmful organic compounds in wastewater becomes the main challenge for many research teams. Cold discharge plasma is one of the most widely studied and developed processes, owing to its low energy cost and easy to operate. The impact of different factors on the decontamination effectiveness of discharge plasma are detailed in this review. The generation and reaction mechanisms of reactive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(73 citation statements)
references
References 142 publications
(180 reference statements)
4
68
0
1
Order By: Relevance
“…e decrease in the removal efficiency with the increase in the electrode distances can be explained as follows: with the increase in the interelectrode distance, the possibility of electrical discharge is reduced, leading to the decrease in the electric-field energy generated to create the plasma and subsequently low production of oxidants during the plasma process. ese results are consistent with those reported in some previous studies [17,38,39]; these studies indicated that a suitable two-electrode spacing from 8 to 20 mm not only improves the formation of oxidants but also accelerates the temperature during the plasma process, leading to the mitigation of a high concentration of pollutants. In the case of COD and ammonia, with the increase in the interelectrode distance, even the removal efficiency decreased, albeit with an insignificant decrease.…”
Section: Effect Of the Initial Phsupporting
confidence: 92%
See 1 more Smart Citation
“…e decrease in the removal efficiency with the increase in the electrode distances can be explained as follows: with the increase in the interelectrode distance, the possibility of electrical discharge is reduced, leading to the decrease in the electric-field energy generated to create the plasma and subsequently low production of oxidants during the plasma process. ese results are consistent with those reported in some previous studies [17,38,39]; these studies indicated that a suitable two-electrode spacing from 8 to 20 mm not only improves the formation of oxidants but also accelerates the temperature during the plasma process, leading to the mitigation of a high concentration of pollutants. In the case of COD and ammonia, with the increase in the interelectrode distance, even the removal efficiency decreased, albeit with an insignificant decrease.…”
Section: Effect Of the Initial Phsupporting
confidence: 92%
“…Recently, the application of cold plasma-one of the AOPs-has attracted considerable attention for wastewater treatment due to its efficiency, less chemical requirements, and low sludge production [17]. Cold plasma has been employed for the degradation of recalcitrant pollutants in the wastewater generated from pesticide production [18], a slaughterhouse [19], textiles [20], and pharmaceuticals [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…[2] One process that has been extensively investigated since then is the oxidation of organic compounds by nonthermal plasma in air or in oxygen-containing gases, with fundamental research in this area being motivated by the interest in developing novel advanced oxidation processes (AOPs) to treat polluted air [3] and water. [4] These studies have provided a deep insight into the discharge-generated reactive species (electrons, molecular excited states, atoms, radicals, ions [5,6] ), which are responsible for the initial attack on the organic pollutants, and into the resulting degradation intermediates and final products. As the aim of such treatments is the complete mineralization of all organic carbon into CO 2 , [7] it is not surprising that discharges and conditions are optimized, so as to achieve as harsh an environment as possible in terms of type and concentration of strong oxidizing reactive species.…”
mentioning
confidence: 99%
“…The authors conveyed that the chemical cocktail consisting of UV radiation and diverse reactive species render non-thermal plasma an adequate treatment method that is economically feasible and has been applied in various areas of environmental remediation. NTP used in combination with adsorbents, catalysts, electrolysis, biodegradation, ultrasonication, ozonisation and ultrafiltration processes could be promising methods for the removal of persistent pollutants and microorganisms from polluted waters, and this was also endorsed by Zeghioud et al [ 134 ].…”
Section: Overview Of the Plasma Processmentioning
confidence: 99%
“…The TOC and COD removal efficiencies 43.0% and 73.7%, respectively demonstrated that the resultant degradation metabolites of OTC were less harmful, and the proposed elimination mechanism pathways demonstrated that OTC was degraded to H 2 O, CO 2, and simpler entities. Complementary investigations on the removal of pharmaceutical residues in water by DBD technologies have been reported [ 134 , 151 , 152 ].…”
Section: Overview Of the Plasma Processmentioning
confidence: 99%